Molecular phylogenetic analysis of Sciadophycus stellatus (Rhodymeniales, Rhodophyta) supports its placement in the family Rhodymeniaceae - Hughey, Jeffery R; Miller, Kathy Ann (Phytotaxa, 2016)
The marine red alga Sciadophycus stellatus E.Y.Dawson (1945) (Figure 1) was described from specimens dredged at 40–50 meters from the Kellett Channel, south shore of Cerros Island (also known as Cedros Island), Baja California, Mexico (Dawson 1945). This uncommon subtidal species occurs in southern California, Baja California, Mexico and Isla Floreana, Galapagos Islands (as Fauchea rhizophylla Taylor) (Dawson 1945, Abbott and Hollenberg 1976, Millar 2001, Aguilar-Rosas et al. 2010). In California, S. stellatus has been collected in San Diego County (UC2003699) and Palos Verdes Peninsula, Los Angeles County (UC1882843), on the mainland coast of southern California and, more commonly, offshore from Santa Catalina (UC1471598), Santa Barbara (UC2034301), Anacapa (WTU-A-012879) and Santa Cruz Islands (UC1965240). In Mexico, in addition to the type locality, it has been collected from Isla Los Coronados (UC1574390), La Bufadora (Aguilar-Rosas et al. 2010), Isla Natividad (UC1882846), Punta Eugenia (US13095) and Bahia Tortugas (US42090), Baja California (distribution records, unless otherwise cited, are based on specimens in herbaria at the University of California at Berkeley [UC], University of Washington [WTU-A], and the Smithsonian Institution [US]).